Sex differences in the brain: Implications for behavioral and biomedical research. (February 2018) - Choleris, Elena; Galea, Liisa A.M.; Sohrabji, Farida; Frick, Karyn M.
Highlights: Sex differences in sex hormone-regulated social behaviors are common. Sex differences may occur in mechanisms through which sex hormones regulate memory. Sex differences in pattern separation is related to hippocampal neurogenesis. Sex differences are seen in stroke incidence, treatment, and responsiveness to treatment. Thus, sex differences should be taken into account in biomedical research. Abstract: Biological differences between males and females are found at multiple levels. However, females have too often been under-represented in behavioral neuroscience research, which has stymied the study of potential sex differences in neurobiology and behavior. This review focuses on the study of sex differences in the neurobiology of social behavior, memory, emotions, and recovery from brain injury, with particular emphasis on the role of estrogens in regulating forebrain function. This work, presented by the authors at the 2016 meeting of the International Behavioral Neuroscience Society, emphasizes varying approaches from several mammalian species in which sex differences have not only been documented, but also become the focus of efforts to understand the mechanistic basis underlying them. This information may provide readers with useful experimental tools to successfully address recently introduced regulations by granting agencies that either require (e.g. the National Institutes of Health in the United States and the Canadian Institutes of Health Research in Canada) or recommend (e.g. Horizon 2020 in Europe) the inclusion of both sexes in biomedical research.